PERBANDINGAN DAN KARAKTERISTIK BEBERAPATES KONVERGENSI PADA DERET TAK HINGGA - Dewi Murni (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2017)
The infinite series is an infinite sum of elements of a sequence of real numbers. A main thing related to the infinite series is to determine its convergence (convergent or divergent). Purpose this research were to analyze and determine a comparison and characteristics of each convergence test, such as: D'Alembert test, Raabe test, Gauss's test, Cauchy's Root Test, and Logarithm Test. A method used descriptive method by analyzing theories relevant to the problems discussed and based on literature study.The results showed that each convergence test had characteristics for its convergence test. The D'Alembert Ratio test is easier to use in a series that contains the formn! ,rn, and nn. Raabe test used if the ratio test obtained value limit comparison is, so the test does not give conclusion. Whereas logarithmic test is used in the infinite series that contains the logarithmic form. The Cauchy n-th root test, can be used to determine the absolute series convergence of the nth power